M-RAS Regulate CDH1 Function in Blastomere Compaction during Porcine Embryonic Development - Dongjie Zhou; Yingjie Niu; Xiang-Shun Cui (The Korean Society of Animal Reproduction and Biotechnology, 2020)
Cell adhesion plays an important role in the differentiation of the morphogenesis and the trophectoderm epithelium of the blastocyst. In the porcine embryo, CDH1 mediated adhesion initiates at compaction before blastocyst formation, regulated post-translationally via protein kinase C and other signaling molecules. Here we focus on muscle RAS oncogene homolog (M-RAS), which is the closest relative to the RAS related proteins and shares most regulatory and effector interactions. To characterize the effects of M-RAS on embryo compaction, we used gain- and loss-offunction strategies in porcine embryos, in which M-RAS gene structure and protein sequence are conserved. We showed that knockdown of M-RAS in zygotes reduced embryo development abilities and CDH1 expression. Moreover, the phosphorylation of ERK was also decreased in M-RAS KD embryos. Overexpression of M-RAS allows M-RAS KD embryos to rescue the embryo compaction and blastocyst formation. Collectively, these results highlight novel conserved and multiple effects of M-RAS during porcine embryo development.